2009
DOI: 10.1159/000189702
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Various Fluoride Compounds and Preparations Thereof on Erosive Tissue Loss in Enamel in vitro

Abstract: Metal fluoride preparations are promising in view of protection against dental erosion. The aim of this study was to screen the effect fluoride preparations containing various polyvalent metal cations had on erosion progression under increasingly severe erosive conditions in human enamel in vitro. Specimens were subjected to a cyclic de- and remineralisation procedure. Demineralisation (experiment E1 and E2a: 6 × 2 min/day, experiment E2b: 6 × 5 min/day) was performed with 0.05 M citric acid (pH 2.3). Fluorida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
78
0
16

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(99 citation statements)
references
References 43 publications
5
78
0
16
Order By: Relevance
“…The efficacy of TiF 4 to reduce carious demineralisation suggested that it might be also an effective agent in preventing erosive dental loss. In several recent in vitro 3,[11][12][13] and few in situ studies 14,15 it was shown that TiF 4 reduced dental erosion significantly and was more effective than sodium, amine or stannous fluoride.…”
Section: Introductionmentioning
confidence: 98%
“…The efficacy of TiF 4 to reduce carious demineralisation suggested that it might be also an effective agent in preventing erosive dental loss. In several recent in vitro 3,[11][12][13] and few in situ studies 14,15 it was shown that TiF 4 reduced dental erosion significantly and was more effective than sodium, amine or stannous fluoride.…”
Section: Introductionmentioning
confidence: 98%
“…[25][26][27] As expected, in the present study, the profilometric analysis showed that the lowest tissue loss was observed in the fluoride-treated group (AmF/NaF/SnCl 2 solution containing 500 ppm F -, 800 ppm Sn 2+ , pH = 4.5) compared to the control group. The tin-containing solution was effective in inhibiting enamel surface loss in other in vitro 4,5,[28][29][30] and in situ 16,31 studies. The erosive tissue loss reduction caused by the fluoride solution (AmF/NaF/SnCl 2 ) compared to no treatment was 60%, which is very similar to the values currently published in the literature.…”
Section: Discussionmentioning
confidence: 84%
“…However, its efficacy is still the object of controversy 1,2 , because little is known about the mechanism of action of fluoride on the prevention and/or control of dental erosion; erosive challenges are much more aggressive than cariogenic challenges and only a thin surface layer, partially demineralized, remains to provide structure for remineralization of eroded surface. 1 Successful results on the reduction of dental demineralization by erosive acids have been shown with polyvalent metal ion-containing products, such as stannous, in several in vitro studies 3,4,5,6,7 and confirmed by other in situ studies. 8,9,10,11 Authors have reported the use of tin-ion in different presentation, such as solutions, toothpastes, gels and varnishes.…”
Section: Introductionmentioning
confidence: 84%
“…Dentre eles, preparações contendo estanho associado a fluoretos provaram ser muito eficazes na redução da desmineralização erosiva (Ganss et al 2004(Ganss et al , 2008(Ganss et al , 2010a(Ganss et al , 2010b(Ganss et al , 2012b(Ganss et al , 2014(Ganss et al , 2015Schlueter et al, 2009aSchlueter et al, , 2009bSchlueter et al, , 2009cSchlueter et al, , 2009dSchlueter et al, , 2009e, 2010Schlueter et al, , 2011aSchlueter et al, , 2013Schlueter et al, , 2014Hove et al, 2006Wiegand et al, 2009;Yu et al, 2010aYu et al, , 2010bComar et al, 2012;Huysmans et al, 2011;Stenhagen et al, 2013;Rakhmatullina et al, 2013;Lussi, 2014).…”
Section: Mecanismo De Ação Dos Fluoretosunclassified
“…Ellingsen, 1994) é atribuída a sua capacidade de reagir com a superfície do dente (Cooley, 1961;Babcock et al, 1978) e modificá-la (Krutchkoff et al, 1972), e este efeito provavelmente resulta em uma maior resistência à desmineralização (Schlueter et al, 2009d (Ganss et al, 2012). com ciclagem ácida é usado.…”
Section: Estanho Associado a Fluoretosunclassified